2018
DOI: 10.1002/ejic.201701272
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Dinuclear AuII and AuI/AuIII Mixed‐Valence Complexes is Directed by Structural Constraints Imposed by Cyclophane‐NHC Ligands

Abstract: Abstract:The oxidation of dinuclear Au I complexes containing cyclophane-bis(NHC) ligands by SOCl 2 , Br 2 and I 2 has been investigated. The outcome of the oxidation was dependent on the nature of the cyclophane-NHC framework. The new complexes were fully characterised by X-ray diffraction and 1 H and 13 C NMR spectroscopy. When the Au I complex contained an ortho-cyclophane framework (dictating short intra-cation Au···Au distances), oxidation resulted in dinuclear Au II complexes of the form X-Au II (NHC) 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…has been previously observed in macrocyclic bis-carbene complexes. [53][54][55] The crystal structure of 24 shows an almost linear ClÀ Au-AuÀ Cl unit (Figure 5), with a AuÀ Au distance (2.5274(3) Å) similar to that of 6 (2.5454(3) Å). The PAu(CF 2 ) 4 AuP chain also adopts a looped conformation, although the PAuAuP dihedral angle (84.827°) is smaller than in 6 because of the conformational constraints imposed by the diphosphine ligand.…”
Section: Macrocyclic Au I Complexesmentioning
confidence: 98%
“…has been previously observed in macrocyclic bis-carbene complexes. [53][54][55] The crystal structure of 24 shows an almost linear ClÀ Au-AuÀ Cl unit (Figure 5), with a AuÀ Au distance (2.5274(3) Å) similar to that of 6 (2.5454(3) Å). The PAu(CF 2 ) 4 AuP chain also adopts a looped conformation, although the PAuAuP dihedral angle (84.827°) is smaller than in 6 because of the conformational constraints imposed by the diphosphine ligand.…”
Section: Macrocyclic Au I Complexesmentioning
confidence: 98%
“…An interesting feature of this class of compounds is the possible presence of intramolecular aurophilic interaction, usually supported by the bridging diNHC ligand [23,24]. When present, aurophilicity can deeply modify the properties of the system, promoting high quality photoemission properties [25][26][27][28][29], and imparting new reactivity of the complexes (e.g., in the oxidative addition of halogens, favoring the formation of gold(II) dinuclear complex with a covalent gold(II)-gold(II) bond) [30][31][32][33]. More recently, we have also started to investigate the possible influence of this interaction in promoting cooperative effects in the catalytic properties of dinuclear gold(I) complexes of general formula Au 2 Br 2 (µ-diNHC) [34].…”
Section: Introductionmentioning
confidence: 99%
“…The most common are dinuclear complexes based on Au(I)-Au(I) interactions, the so-called aurophilic interaction. [5][6][7][8][9][10] Dinuclear complexes in which Au (II)-Au(II), Au(III)-Au(III) and mixed Au(I)-Au(III) interactions occur are also known, [11][12][13] and for mixed Au(I)-Au(III) complexes the aurophilicity was found to play a role. 14,15 It may be also concluded that dinuclear Au(II)-Au(II) complexes are more stable than Au(II) mononuclear complexes, since the formation of Au-Au bond stabilizes the Au(II) centres.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 It may be also concluded that dinuclear Au(II)-Au(II) complexes are more stable than Au(II) mononuclear complexes, since the formation of Au-Au bond stabilizes the Au(II) centres. 1,13,[16][17][18] Mass spectrometry plays an important role in the field of gold chemistry. A number of spectacular Au clusters have been studied using mass spectrometry, namely AuV 2 O 6 þ , 19 Au m Fe n þ/-…”
Section: Introductionmentioning
confidence: 99%